PUBLIC RELATIONS ACTIVITIES IN MALAYSIAN ISLAMIC BANKING: THE CASE OF BANK ISLAM MALAYSIA BERHAD (BIMB) - Neneng Ela Fauziyyah; Erna Farina Binti Mohamed (Airlangga International Journal of Islamic Economics and Finance, 2020)
The public relations concept is a basic concept that must exist in various organizations. The strategy taken might be affected by or affect a cultural image. In the current world, Islamic institutions have emerged and grown rapidly. In particular, in the financial industry, Islamic banking in Malaysia has become a pioneer and evidently survives within the industry. Having said that, the public relations concept supposes to engage within their activities, also. But then, as Islamic values are being their foundation, it might influence their public relations strategy. Hence, the objective of this study is to observe the Islamic values that influencing the public relations and the cultural image strategy of the Islamic institution which primarily is Bank Islam Malaysia Berhad (BIMB). We chose them because Bank Islam is a first and pioneer of Islamic banking in Malaysia that expected to be a very Islamic banking version. By using a case study approach dependent on a circuit of culture (COC) model, this study found that Bank Islam as full-pledge Islamic banking has engaged with Islamic culture in their business activities and well-done in applying public relations strategies. Five elements of the COC framework consist of regulation, production, consumption, representation, and identity have been interlinked with the annual report as well as Bank Islam’s website.